2015
DOI: 10.1186/s12891-015-0719-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the outcomes of cannulated screws vs. modified tension band wiring fixation techniques in the management of mildly displaced patellar fractures

Abstract: BackgroundK wire fixation with tension band wiring has conventionally been used for the open reduction and internal fixation of the patella. However, it suffers from distinct disadvantages such as implant irritation, need for open reduction, incidence of palpable implants, and need for subsequent implant removal. A smaller incision with percutaneous fixation may be an alternative to this established conventional technique. Thus, the purpose of this trial was to compare the treatment outcomes of patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…The commonest fracture configuration in humans is transverse, usually due to trauma, although stress fractures are also reported (4). In human orthopaedics, a large number of fixation methods for patellar fractures have been described (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The commonest fracture configuration in humans is transverse, usually due to trauma, although stress fractures are also reported (4). In human orthopaedics, a large number of fixation methods for patellar fractures have been described (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our results showed that 21.4% of K-wire group patients experienced protrusion of fixation material under the skin. The ends of K-wires stimulated the soft tissue and caused pain, thus affecting performance in early functional exercise of the knee, 26 which was not beneficial to knee joint function. Pain caused by the K-wires can lead to hardware removal, rates of which have been reported to range from 37 to 55% for transverse patellar fractures 27 ; the pain is the main reason for such removal.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are new techniques such as cannulated screw tension band [11,12] system [13] and patella plate [14], the MTBW is still the most widely accepted surgical method for the treatment of patellar transverse fracture [7]. The MTBW technique is easy to operate on and economical to reduce the burden on patients, and the key of MTBW technique is to keep two k-wires parallel [8,15].…”
Section: Discussionmentioning
confidence: 99%